In vitro bioactivities and formulation stability of Houttuynia cordata essential oil for cosmetic applications - Sangthong, Sarita; Chaiwut, Phanuphong; Pintathong, Punyawatt; Suwannawong, Benjarat; Srisayam, Montra; Theansungnoen, Tinnakorn; Chandarajoti, Kasemsiri; Arabnozari, Hesamoddin; Sarker, Satyajit D; Nahar, Lutfun (Scientific reports, 2025)
Houttuynia cordata essential oil (HCEO) is a promising ingredient for acne-focused phytocosmetics. This in vitro study evaluated its volatile compounds, antimicrobial, antioxidant, wound-healing, anti-melanogenic, and anti-inflammatory properties, along with the stability of topical oil‑in‑water emulsions. GC-MS analysis identified n-decanoic acid (46.21%), β-myrcene (14.082%), and 2-undecanone (11.01%) as the main components. HCEO inhibited the growth of Staphylococcus aureus, Candida albicans, Staphylococcus epidermidis, and Cutibacterium acnes. It displayed antioxidant activity, with IC50 values of 13.25 ± 0.09 mg/mL (DPPH) and 17.44 ± 0.16 mg TEAC/g (FRAP). No cytotoxicity was observed in NIH/3T3 fibroblasts and RAW 264.7 macrophages (up to 500 µg/mL). HCEO enhanced fibroblast migration by 26.94% ± 1.12% at 400 µg/mL. It inhibited melanin synthesis in B16F10 and A375 cells, with IC50 values of 200.61 ± 2.19 and 152.16 ± 1.97 µg/mL, respectively, and tyrosinase activity (IC50 of 48.00 ± 0.01 µg/mL). Additionally, HCEO suppressed nitric oxide production in LPS-stimulated macrophages (IC50 of 1.176 ± 0.084 µg/mL). Oil-in-water emulsions containing HCEO maintained physical stability for eight weeks, indicating suitability for cosmetic product development. These findings suggest HCEO has potential as a natural ingredient for advanced skincare formulations targeting acne and skin inflammation, although further work is needed to optimise loading, assess skin permeation, and confirm efficacy in vivo.
Keywords: Wound healing; antiinfekční látky; Antioxidants; Anti-melanogenesis; myši; Houttuynia; Oils, Volatile; antioxidancia; buňky NIH 3T3; Humans; Antimicrobial; zvířata; hojení ran; Animals; Mice; NIH 3T3 Cells; Cosmetics; Wound Healing; Phytocosmetics; antiflogistika; Houttuynia cordata essential oil; oleje prchavé; Antioxidant; RAW 264.7 Cells; lidé; Anti-Inflammatory Agents; kosmetické přípravky; RAW 264.7 buňky; Candida albicans; Anti-Infective Agents